PENCEGAHAN FISSURE SEALING PADA MASYARAKAT DI PESISIR PANTAI KELURAHAN OESAPA - Friska D. Simamora; Manginar Sidabutar; Novianti P. Baunsele (Bajang Institute, 2025)
Dental caries is a disease of hard tooth tissue that begins with decalcification of the inorganic structure of the teeth. The results of the 2018 Riskesdas show that the prevalence of the DMFT index in Indonesia has increased the DMF-T index to >6 from the 2013 Riskesdas results with a DMF-T index of 4.6 and increases with age. The results of the 2018 Riskesdas show that the prevalence of caries in Indonesia in 2018 reached 45.3%. Fissure sealant is a preventive protection for teeth that have deep pits and fissures which are therefore more susceptible to caries, by applying a filling material (sealants) to the occlusal surface which aims to prevent dental caries. Objective achieved from the Community Service activity is to reduce the number of dental caries by taking preventive measures Fissure sealing in children on the coast of Oesapa. The results of the data above show that from interviews with parents there are still those who give bottled milk when their children sleep so that in the results of the examination of children who have more than 5 teeth have caries so that there is a rampant caries in children. In this community service, it was also conveyed the importance of regulating the pattern of giving bottled milk to children, not when the child is sleeping and after giving milk, the child's mouth and teeth must be cleaned. The conclusion of prevention of fissure sealant in children at the integrated health post is that it needs done to prevent tooth decay, especially in children where this action taken to cover deep fissures in the teeth. This action is one way to prevent tooth decay. In this activity, counseling was also provided to brush teeth properly, foods that damage teeth and importance of routine checks at dental health facilities.